Eco-enzyme as disinfectant: a systematic literature review - Vidalia, Cindy; Angelina, Emily; Hans, Joenni; Field, Lin Hill; Santo, Nathania Caroline; Rukmini, Elisabeth (International Journal of Public Health Science (IJPHS), 2023)
COVID-19 increases the awareness of cleanliness and sanitation in society. Trends in launching sanitizer and disinfectant products have risen significantly to meet customer demand. However, the existing commercial sanitizer products are mostly chemical-based and may cause adverse effects. Therefore, eco- enzyme is a perfect bio-waste utilization for nonchemical-based sanitization products. The authors investigated eco-enzymes' effectiveness in an aerosol spray from fruit waste for a pleasant natural disinfectant. This review aimed to compile results from previous studies on fruit waste by systematically reviewing empirical studies on household waste practices to develop an eco-enzyme following the PRISMA guidelines. A digital search in five databases from Google Scholar, PubMed, Garuda, Sinta, and Open Alex resulted in 24 relevant journals, considering keywords such as eco-enzyme, disinfectant, and organic waste. The mapping results show that eco-enzyme is feasible and economical for disinfecting and sanitizing surfaces due to its antimicrobial activity. The presence of acetic acids and enzymes (i.e., lipases and amylases) can inhibit specific strains of microorganisms, namely Escherichia coli and Enterococcus sp.